Plano de comunicação para a garagem naútica Poço do Robalo - Souza, Iolanda Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of this study is the elaboration of a communication plan for a nautical garage located in Bertioga: Poço do Robalo. The organization has existed since 1996 and has never invested in communication. The need of a scenario analysis and elaboration of a strategic planning comes especially due to the moment of crisis that has passed the Brazilian society, in which many organizations are in recession and losing their clients. The communication plan is based on a theoretical contribution about the subject, the analysis of the organization's scenarios, the survey with clients and about competition, in order to materialize the proposals of communication actions that aims to improve the relationship with their stakeholders. It is worth mentioning that because it is a small organization, the whole process is based on the viability of the strategies, not only to contribute to the communication but to the business itself. As a result, it is verified that only the analysis of the organizational situation has already brought a new posture to the owners who realized the importance of relationships and communication in their business, accepting the implementation of the plan in the immediate future

O estudo tem como objetivo a elaboração de um plano de comunicação para uma garagem náutica localizada em Bertioga: o Poço do Robalo. A organização existe desde 1996 e nunca investiu em comunicação. A necessidade de uma análise de cenários e da elaboração de um planejamento estratégico surge especialmente pelo momento de crise que vem passado a sociedade brasileira, no qual muitas organizações estão em recessão e perdendo seus clientes. O plano de comunicação construído surge a partir de um aporte teórico sobre o assunto, análise de cenários da organização e da concorrência e levantamento de opiniões junto a clientes, com objetivo de materializar as propostas de ações de comunicação que tem como intuito melhorar o relacionamento desta com seus públicos de interesse. Vale destacar que por ser uma organização de pequeno porte, todo o processo é pautado na viabilidade das estratégias, no sentido não só de contribuir para a comunicação mas para o negócio em si. Como resultado verifica-se que só a análise da conjuntura organizacional já trouxe uma nova postura aos proprietários...
Keywords: Comunicação; Planejamento estratégico; Pescaria; Strategic Planning